Peningkatan Kapasitas Diagnosis Foto Thoraks Covid-19 dengan Aplikasi Adobe Photoshop Express - Muslim Andala Putra; Ahmad Mochtar Jamil; Muhammad Anas (Universitas Muhammadiyah Surabaya, 2020)
AbstracCovid-19 is a new viral infectious disease. The first appeared in Wuhan and became apandemic in 2 months. Clinical diagnosis is confirmed by fever, cough, shortness of breath,combined with lymphocyte neutrophil ratio examination and radiology imaging with chest Xray or chest C.T. with a ground-glass appearance. C.T. scans are not widely available inIndonesia hospital. Many hospitals only own X-Ray as radiologic diagnostic imaging for covid-19. Adobe Photoshop Express with digital imaging capabilities can improve the ability todiagnose Covid-19 from chest X-Ray because of software similarity like the radiologicworkstationKeyword: photoshop, covid-19, thorax plain x-ray, diagnosis, image